13 Medical Students' Mood Adversely Affected By COVID-19 Pandemic: An Interim Analysis from the SPICE-19 Prospective Cohort Study Of 2075 Medical Students and Interim Foundation Doctors. (4th May 2021) - Bandyopadhyay, S; Georgiou, I; Baykeens, B; Gillespie, C; de Andres Crespo, M; Bashir, M; Handa, A; Saunders, K
Abstract: Introduction: In order to appropriately support medical students and foundation year doctors, it is imperative that we understand the impact the COVID-19 pandemic has had upon them. This study assessed the effects of the COVID-19 pandemic on medical students and interim foundation year doctors across the United Kingdom (UK), and the support that they received and sought. Method: A prospective, observational, multicentre study was conducted. All medical students and interim foundation year doctors were eligible to participate. Results: A total of 2075 individuals participated. There was a decrease in participants' mood when comparing their mood before the pandemic to during the pandemic (p < 0.0001). Social distancing negatively impacted the mood of the greatest number of participants. All areas of life included in the study were found to have been significantly more negatively impacted than positively impacted (p < 0.0001). 931 participants wanted more support from their university. Conclusions: When medical students return to their universities, there is likely to be a need for enhanced wellbeing support, adaptations in the short-term and long-term strategies for medical education, and provision of financial guidance. If no action is taken, there may be a knock-on effect on workforce planning and the health of our future workforce.